Organic σ-Hole Containing Crystals with Enhanced Nonlinear Optical Response and Efficient Optical-to-THz Frequency Conversion - Kim, Se In; Kim, Won Tae; Seok, Jin Hong; Jazbinsek, Mojca; Yoon, Woojin; Yu, In Cheol; Yun, Hoseop; Kim, Dongwook; Rotermund, Fabian; Kwon, O. Pil (Advanced Optical Materials, 2020)
A new approach for the molecular design of highly efficient nonlinear optical organic crystals is proposed by introducing substituents that form σ-holes on both nonlinear optical cationic chromophores and aromatic anions. Introducing chlorinated substituents, in which a relatively positive σ-hole and a negative belt coexist, provides selective reduction capability of specific π–π intermolecular interactions and simultaneous multiple secondary bonding capabilities. This leads to a crystalline state with enhanced first-order hyperpolarizability βcrystal of chromophores that favors parallel chromophore alignment and suppression of molecular vibrations, which are optimal characteristics for electro-optic and nonlinear optical applications, including efficient THz wave generation. Compared to benchmark nonhalogenated and fluorinated analogous crystals with state-of-the-art macroscopic optical nonlinearity, σ-hole containing chloro-quinolinium crystals exhibit up to two times higher macroscopic nonlinear optical response and remarkably different crystal characteristics. As a result, a 0.16 mm thick chloro-quinolinium crystal exhibits ≈22 times higher optical-to-THz conversion efficiency than the widely used 1.0 mm thick ZnTe inorganic crystal. Moreover, chloro-quinolinium crystals exhibit very broad THz spectra, up to 8 THz with significantly different THz spectral shape compared to benchmark organic crystals, which is attributed to different phase matching between optical and THz frequencies and molecular vibration motions.
Keywords: Crystal characteristics; First-order hyperpolarizability; Intermolecular interactions; Nonlinear optical applications; Nonlinear optical response; Optical nonlinearity; Organic crystal; Selective reduction; nonlinear optics; organic crystals; terahertz waves